KNOWLEDGE AS DETERMINANTS INCREASE CLEAN AND HEALTHY LIVING BEHAVIORS AMONG STUDENTS IN GENERAL PRIMARY SCHOOL 07 LANDAU-LEBAN SUB DISTRICT MELAWI IN 2015 - Sriwidodo, Sriwidodo; Santosa, Santosa (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Clean and Healthy Lifestyle (CHLB) is an attempt to empower students, teachers and schools to know, understand and be able to practice CHLB and play an active role in creating a healthy behavior in school. The preliminary data survey indicated a needs to improve CHLB behavior among children in General Primary School 07 Landau-Leban Sub District Melawi. Aims: This study aimed to determine the relationship between gender, age, knowledge, attitudes, beliefs, and also the roles of teachers, parents and the School Health Unit (UKS) to CHLB in SDN 07 Landau-Leban Melawi West Kalimantan in 2015. Methods: The study design was cross-sectional study. The population in this study was 82 students of class IV, V and VI. The statistical test used Chi Square and Multiple Logistic Regression. During data collection, two teachers assisted the programs to the students. Results: This study showed that 45 students (54.9%) have low CHLB behavior. This behavior is related to knowledge, attitude and role of the teacher. The most dominant variable related to CHLB is knowledge (OR 5.434) Conclusion: Students with high knowledge tend to have more than 5 times greater CHLB. The findings suggest a need to increase students knowledge of CHLB in the form of counseling, provision of facilities and infrastructure (sink, anti-septic, healthy canteen, bins, and promotional media such as posters). Improving CHLB to the students requires schoolâs support to provide training incorporated with relevant health facilities.Â